Floral dimorphism in plant populations with combined versus separate sexes - Yakimowski, Sarah B. (Oxford University Press, 2011)
BACKGROUND AND AIMS: Dimorphism among floral traits can evolve through variation in selection intensity between female and male performance, especially when sex functions are separated between flowers on a plant (monoecy), or between individuals (dioecy). In animal-pollinated species, male floral traits are predicted to be larger because competition for pollinators should favour larger displays. Floral dimorphism may be greater in dioecious than monoecious populations because of trade-offs between female and male function and opportunities for selfing in hermaphrodites. METHODS: These predictions were tested by surveying flower size, total flowers per inflorescence and daily display size in the insect-pollinated Sagittaria latifolia (Alismataceae). This species is useful for comparative analysis because populations are mostly either monoecious or dioecious. We examined floral dimorphism in 13 monoecious and 16 dioecious populations in eastern North America. KEY RESULTS: Male flowers were significantly larger than female flowers in monoecious and dioecious populations, but there was no evidence for greater flower size dimorphism in dioecious populations despite their larger flower sizes overall. Although inflorescences in both dioecious and monoecious populations produced more male flowers, daily floral displays were significantly larger for female than male function due to more synchronous female flower opening. Daily floral display dimorphism was significantly greater in dioecious populations, due to greater female daily floral displays. There was a positive relationship between mean flower size and total flowers per inflorescence for both sexes in dioecious populations, but no relationship for either sex function in monoecious populations. Flower size dimorphism was positively correlated with the frequencies of females in dioecious populations. CONCLUSIONS: The increased size and number of male flowers and protracted male floral displays in S. latifolia are probably shaped by sexual selection for more effective pollen dispersal.